Impact of Physical Violence on the Mental Health of the Nurses Working in the Teaching Hospitals of Al-Dewaniya City, Iraq - Hamzah, Zinah Razzaq; Al-Ameri, Maan Hameed Ibrahim (International Journal of Psychosocial Rehabilitation, 2020)
Objective: To identity workplace violence and mental health among nurses, to find out the impact of workplace violence on the mental health of nurses, and to determine the relationship between levels of workplace violence and levels of mental health with nurses’ demographic characteristics.Methodology: Descriptive analytic study was conducted on a convenience sample of nurses working in teaching hospitals at Al-Dewaniya city in Iraq. Data are collected January 20th 2020 through March 15th 2020.Results: A total of 250 nurses completed the questionnaire, 64.8% of participants had been experienced at least one kind of violence, the majority of sample who experience workplace violence were female nurses about sixty-one and six percentage: 32.8% to physical violence, patients' relatives (87.6%) were identified as the primary perpetrators of violence. Participants exposed to workplace violence effect on their mental health about (55.6%) were intermediate levels of mental health.Conclusions: The characteristics of the present study indicated that most of the nurses who are exposed to workplace violence and that's effected on their mental health were females within the age group between (20-29) years old were married concerning the association between socio-demographic characteristics and workplace violence. There was no relationship between gender, age, and level of education, ward, Years of experience, and workplace violence. However, there was an association between marital statuses.Recommendations: The study recommends the ministry of health and environment, and related legal and executive parties must construct, adopt and issue special law to protect all health workers in general and nurses in specific against all types of work-related violence. Nurses who have experienced violence during their work should be granted leave in order to alleviate the psychological effects that will appear on them because of their exposure to violence.